Qualitative and Quantitative Determination of Dapagliflozin Propanediol Monohydrate and Its Related Substances and Degradation Products Using LC-MS and Preparative Chromatography Methods - Ali Ismail; Mohammad Haroun; Youssef Alahmad (مجلة بغداد للعلوم)
Dapagliflozin is a novel sodium-glucose cotransporter type 2 inhibitor. This work aims to develop a new validated sensitive RP-HPLC coupled with a mass detector method for the determination of dapagliflozin, its alpha isomer, and starting material in the presence of dapagliflozin major degradation products and an internal standard (empagliflozin). The separation was achieved on BDS Hypersil column (length of 250mm, internal diameter of 4.6 mm and 5-μm particle size) at a temperature of 35℃. Water and acetonitrile were used as mobile phase A and B by gradient mode at a flow rate of 1 mL/min. A wavelength of 224nm was selected to perform detection using a photo diode array detector. The method met the requirement of the International Conference on Harmonisation for Registration of Pharmaceuticals for Human Use (ICH) for validation. The molecular weight of impurities and degradation products was estimated using positive ESI-MS. Fifteen impurities were detected during the analysis of dapagliflozin APIs and the brand Farxiga ® and some generic products. Three of fifteen detected impurities (H, J and K) exceeded the impurities acceptable limits 0.1%. Those impurities were isolated using new preparative chromatography then characterized using elemental analysis, FTIR and NMR.